Formation of the Russian Federation as a secular state (XVII century - beginning of the XXI century): historical and theoretical aspects (Stato, Chiese e pluralismo confessionale, 2015)
Article peer reviewedSOMMARIO: 1. Introduction - 2. Pre-revolutionary period - 3. The Soviet period -4. Modern stage - 5. Conclusion. Abstract: The article examines main stages of formation of the secular state in the Russian Federation. The author provides historical and legal overview of the development of secularism in Russia in the period starting from 1701 to the present days.